Science and Business Cooperation. Barriers in Poland Within the Context of Selected European and North American Countries - Trzmielak Dariusz (Marketing of Scientific and Research Organizations, 2015)
This article focuses on the theoretical and empirical analysis of factors affecting the cooperation between science and business. The author will present the results of empirical research conducted in Poland, the Czech Republic, Hungary, France, Norway, the United States of America and Canada. The analysis will indicate how and which factors: structural, systemic, competence or awareness and cultural can be utilised in the commercialisation of knowledge and technologies. The analysis of research outcomes which underpins this study is also set on the following assumptions: